2014
DOI: 10.1111/jog.12538
|View full text |Cite
|
Sign up to set email alerts
|

Case of minimal deviation adenocarcinoma: Possible clinical link to lobular endocervical glandular hyperplasia as its origin

Abstract: Minimal deviation adenocarcinoma (MDA) is defined as an extremely well differentiated variant of endocervical adenocarcinoma. Several reports have stated that MDA associates with lobular endocervical glandular hyperplasia (LEGH). It is difficult to distinguish LEGH from MDA based on clinical and histologic similarities. There is no definite evidence proving that LEGH is a precursor lesion of MDA. A 45-year-old woman was admitted to our hospital for minute investigation of her neurological disorder. The multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…10 This is consistent with a previous report. 13 The present study suggests the importance of cytologic change rather than size change. However, it should be noted that two lobular endocervical glandular hyperplasia cases also showed worsening cytology, and some may be associated with an increase in size and worsening cytology, suggesting that the detection of worsening cytology in association with increased lesion size does not necessarily indicate the presence of malignancy.…”
Section: Discussionmentioning
confidence: 56%
“…10 This is consistent with a previous report. 13 The present study suggests the importance of cytologic change rather than size change. However, it should be noted that two lobular endocervical glandular hyperplasia cases also showed worsening cytology, and some may be associated with an increase in size and worsening cytology, suggesting that the detection of worsening cytology in association with increased lesion size does not necessarily indicate the presence of malignancy.…”
Section: Discussionmentioning
confidence: 56%
“…Sugihara et al reported a case that was initially diagnosed as LEGH, but histologically diagnosed as MDA after a 2-year follow-up, which revealed an increase in the size of the lesion (from 21 mm to 31 mm in diameter), and the deterioration of the Pap smear. 28 They concluded that the deterioration of Pap smear findings and increase in lesion size were important signs of the malignant progression of LEGH lesions to MDA. Therefore, we consider changes in MRI findings and cytology as the hallmarks of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no reliable markers to detect the early stage of malignant transformation. In this regard, an informative report 45 and our report 44 suggested that an increase in lesion size and worsening cytology were important markers to detect malignant change of LEGH. In reference with these reports, we also carefully followed up 69 cases of clinical LEGH, we found one MDA patient.…”
Section: Clinical Managementmentioning
confidence: 68%
“…NC cases generally show NILM, whereas most MDA/GAS shows AGC‐FN, AIS, or adenocarcinoma. Especially, AGC‐NOS suggested benign (nonatypical) LEGH, whereas AGC‐FN suggested atypical LEGH or MDA/GAS 44,45 . Collectively, cervical cytology is useful to distinguish benign LEGH and MDA/GAS/atypical LEGH 14,26,42 .…”
Section: Clinical Managementmentioning
confidence: 99%
See 1 more Smart Citation